Characterization of carbon nanotube doped PEDOT:PSS thin film devices - Yip, W.S.; Woon, Kai Lin (National Institute of Optoelectronics, 2010)
ITO/PEDOTOPSS/Al devices containing dispersed Carbon Nanotubes (CNTs) and pure PEDOT:PSS are compared. It was found that the conductivity of each CNT doped PEDOT: PSS film was reduced upon application of 20Hz pulses of -20V at reversed bias. Deformation of the aluminium electrode was found to occur upon application of voltage on the PEDOT: PSS film. However, no aluminium electrode deformation occurs on CNT-doped PEDOT: PSS films. This was verified by Scanning Electron Microscope (SEM). Depth profiling by Auger spectroscopy indicated high level of oxidation at the aluminium PEDOT: PSS interface for device with pure PEDOT: PSS but significantly less with PEDOT doped with CNTs. Resistance is found to vary in periodic high/low values dependent on direction of voltage sweep.